Effects of the disconnection technique and preemptive one-lung ventilation on lung collapse during one-lung ventilation in thoracoscopic surgery - Hongru Zhang; Silin Xiang; Longyong Mei; Yonggeng Feng; Han She; Yi Hu; Li Wang (BMC Anesthesiology)
Abstract Background During thoracoscopic surgery with one-lung ventilation (OLV), achieving lung collapse is critical for providing surgeons with a good visibility of the surgical field and to minimise tissue compression. The aim of this study was to evaluate the efficacy of both the disconnection technique and preemptive one-lung ventilation in facilitating lung collapse during thoracoscopic surgery using a double-lumen tube (DLT). Methods Ninety-seven eligible patients were included and randomly divided into three groups. Control group: OLV was initiated when the surgeon started the skin incision and exposed the operative side. Disconnection group: OLV was started two minutes after the DLT was disconnected, this procedure started when the surgeon performed the skin incision. Preemptive group: OLV was initiated promptly after the patient was turned to the lateral position, and the bronchial tube port was clamped on the operative side at the lateral position for no less than 6 min until the pleura was opened. The primary outcome was the time to achieve satisfactory lung collapse, defined as the time required to reach a lung collapse score of eight points. The secondary outcomes included the lung collapse scores at different time points, Pleural opening times, OLV times, blood gas analysis results and the incidence of hypoxemia and pulmonary complications. The hypothesis formulated before data collection was that both the disconnection technique and preemptive OLV decrease the time to satisfactory lung collapse. Results Compared to the control group, both the disconnection and the preemptive group had a shorter time to satisfactory lung collapse (P < 0.001), lung collapse in the preemptive group was superior to that in the disconnection group at one minute (P = 0.045), no significant differences were found among the three groups in terms of other outcomes. Conclusion Both the disconnection technique and preemptive OLV decrease the time to satisfactory lung collapse. However, preemptive OLV results in superior early lung collapse and is therefore may more suitable for clinical application than the disconnection technique. Trial registration The protocol of this study was registered at www. chictr. org. cn (29/07/2022, ChiCTR2200062199).